Changing trends and pretravel preparation of business travelers from Greece during the financial crisis. (March 2019) - Pavli, A.; Lymperi, I.; Minitsios, T.; Katerelos, P.; Souli, M.; Ouzounidou, Z.; Maltezou, H.C.
Summary: Objectives: Unemployment in Greece has been increasing as a result of the financial crisis. The aim of this study was to assess the changing trends of business travelers and their pretravel preparation. Study design: Prospective, questionnaire-based study. Methods: The study was conducted between 2008 and 2016 at all Regional Public Health Departments. All travelers seeking pretravel advice during the study period were invited to participate. Results: A total of 12, 379 travelers completed the questionnaire, 58% of whom were business travelers. Between 2008 and 2016, the proportion of business travelers increased from 33% to 80.7% and those travelling for recreational purposes decreased from 47.9% to 15.5%. Business travelers sought pretravel advice at a mean of 18.5 days before departure; 89.1% were men with a mean age of 34.4 years. The Middle East was the most common destination (47.8%) followed by Sub-Saharan Africa (28.3%). Most business travelers stayed in urban areas (77.6%) and for ≥ 1 month (68.6%). Yellow fever vaccine was administered to 75% of business travelers. A total of 76.2%, 26.9%, 15.5%, and 13.9% of those visiting Sub-Saharan Africa received yellow fever, typhoid fever, hepatitis A, and meningococcal vaccines, respectively. Malaria prophylaxis vaccine was administered to 26.8% of business travelers; including 46.5% of those traveling to Sub-Saharan Africa and 53.5% to those traveling to the Indian subcontinent. Conclusions: There is an increasing trend for business travel from Greece, especially to developing countries. Improving the knowledge of travel health consultants about the risks of business travel and the pretravel preparation of business travelers is crucial. Highlights: Business travelers account for 58% of those seeking pretravel services. The proportion of business travelers increased from 33% to 80.7% between 2008 and 2016. Business travelers sought pretravel advice a mean of 18.5 days before departure. The Middle East and Sub-Saharan Africa were their most common destinations. Malaria prophylaxis was given inadequately to Sub-Saharan African travelers.